21st Kilbrandon Lecture - Phil Scraton (Scottish Journal of Residential Child Care)
It is more than 25 years since publication of ‘Childhood’ in ‘Crisis,’? (Scraton, 1997), a collection of essays written by members of the Young People, Power and Justice Research Group, formed following the killing of James Bulger in Liverpool. The trial in an adult court of two 10-year-old children, convicted of murder and publicly named, created an unprecedented and vitriolic reaction in the media and from politicians of all parties. The text mapped the negative impact on legislation, state policies and professional practice. In the wake of moral panics regarding escalating crime, ‘no-go’ areas and a rising ‘underclass’, a rare case was portrayed as the extreme end of a continuum of children’s aberrant behaviour and parental neglect.